Dalak Tirozin Kinaz ve Histon Deasetilaz Enzim İnhibisyonunun FLT3-ITD(+) Akut Miyeloid Lösemi Hücreleri Üzerindeki Anti-Lösemik Etkisi - Akcok, E. Basak Gencer; Şansaçar, Merve (My University, 2025)
Spleen Tyrosine Kinase (Syk) crosstalk with paramount signaling pathways which has a major contribution in the progress of acute myeloid leukemia (AML) such as PI3K, NFκB and JAK/STAT signaling pathways. Several studies recorded that deregulated Histone Deacetylase (HDAC) enzymes are involved in the pathogenesis of AML. The study aims to reveal the effect of Syk and HDAC co-inhibition on MOLM-13 and MV4-11 AML cells which are harboring the receptor of FMS-like Tyrosine Kinase's (FLT3) Internal Tandem Duplication (ITD). AML cells were incubated using both R406 and HDAC inhibitors alone and in combination, and increasing concentrations of R406 and HDAC inhibitors revealed a significant reduction of MOLM-13 and MV4-11 cells’ viability using MTT cell viability test. Furthermore, the combination of R406 and VPA resulted in a reduction in the proliferation of both cells correlated with the synergistic effect of the two drugs revealed by the combination index (CI). Moreover, investigating apoptosis for the combined administration of drugs resulted in induced apoptosis in AML cells using Annexin-V/PI double staining. We observed also changes in the mRNA expression level of MYC after combination treatment via Real-time PCR analysis. Even though further studies are needed, targeting Syk and HDAC enzymes in AML cells may be a good strategy in the treatment of patients suffering from AML with FLT3 ITD (+) mutation.

Öz: Dalak Tirozin Kinaz (Syk), akut miyeloid lösemi (AML) gelişiminde büyük katkısı vardır ve PI3K, NFκB ve JAK/STAT sinyal yolları gibi başlıca sinyal yolaklarıyla çapraz iletişim kurar. Birçok çalışma, bozuk Histon Deasetilaz (HDAC) enzimlerinin AML patogenezinde rol oynadığını kaydetmiştir. Çalışmanın amacı, Syk ve HDAC ko-inhibisyonunun, FMS benzeri tirozin kinaz reseptöründe (FLT3) İç Tandem Duplikasyonu (ITD) barındıran MOLM-13 ve MV4-11 AML hücreleri üzerindeki etkisini ortaya koymaktır. AML hücreleri hem R406 hem de HDAC inhibitörleri ile tek başına ve kombinasyon halinde inkübe edildi ve inhibitörlerinin artan konsantrasyonlarının, MTT hücre canlılığı testi ile MOLM-13 ve MV4-11 hücrelerinin çoğalmasında önemli bir azalma olduğu ortaya konuldu. Ayrıca, R406 ve VPA kombinasyonu, kombinasyon indeksi (CI) tarafından ortaya çıkarılan iki ilacın sinerjistik etkisiyle ilişkili olarak her iki hücrenin proliferasyonunda bir azalmaya neden oldu. Ayrıca, Annexin-V/PI çift boyama yöntemi kombinasyon çalışmasının AML hücrelerinde apoptozu indüklekledini gösterdi. Ayrıca, Gerçek zamanlı PCR analizi ile kombinasyon tedavisinden sonra MYC'nin mRNA ekspresyon seviyesinde değişiklikler gözlendi. Daha fazla çalışmaya ihtiyaç duyulmasına rağmen, AML hücrelerinde Syk ve HDAC enzimlerini hedeflemek, FLT3 ITD (+) mutasyonu olan AML hastalarının tedavisinde yeni bir strateji olabilir.
The Anti-Leukemic Effect of the Inhibition of Spleen Tyrosine Kinase and Histone Deacetylase Enzyme Inhibition on the FLT3-ITD(+) Acute Myeloid Leukemia Cells
Keywords: Onkoloji; Mikrobiyoloji